Regional left ventricular myocardial work index in culprit territory predicts early left ventricular remodelling in patients with st-segment elevation myocardial infarction. (25th November 2020) - De Paula Lustosa, R; Van Der Bijl, P; Knuuti, J; Goedemans, L; El Mahdiui, M; Montero-Cabezas, J; Kostyukevich, M; Fortuni, F; Ajmone Marsan, N; Bax, J.J; Delgado, V
Abstract: Background: The association between left ventricular (LV) myocardial work index (LVMWI) derived from speckle tracking echocardiographic strain data in combination with non-invasive blood pressure recordings and adverse LV dilatation i.e. remodelling has not been evaluated. Purpose: To assess the predictive value of regional LVMWI for LV remodelling at baseline echocardiography in patients with ST-segment elevation myocardial infarction (STEMI). Methods: This retrospective study included 350 patients (265 men, mean age: 61±10 years) with STEMI treated with primary percutaneous coronary intervention and optimal medical therapy. Clinical variables, conventional echocardiographic parameters, global and segmental measures of LVMWI were recorded at baseline. The primary endpoint was early LV remodelling defined as increase in LV end-diastolic volume (LVEDV) ≥20% at 3 months after the index event. Results: Eighty-seven patients (24.9%) presented with early LV remodelling. The global and regional LVMWI in the culprit territory were significantly lower in patients with early LV remodelling. Univariate and multivariate logistic regression analyses were performed to identify predictors of early LV remodelling. At the index event, troponin I peak, LVEDV and LVMWI in the culprit territory were independently associated with early LV remodelling (Table). Conclusions: In STEMI patients treated with primary percutaneous coronary intervention and optimal medical therapy, the regional LVMWI in the culprit territory at echocardiography before discharge is independently associated with troponin I peak and LVEDV in predicting early LV remodelling. Funding Acknowledgement: Type of funding source: Other. Main funding source(s): European Society of Cardiology